Evaluation of pre-test counselling offered for non-invasive prenatal testing (NIPT) as a primary screening tool - Ho Yin Diana Lee; Lin Wai Chan (Taylor & Francis Group, 2023)
The increasing popularity and expansion of non-invasive prenatal testing (NIPT) to screen for rare conditions beyond common trisomies prompts evaluation of pre-test counselling currently offered. We conducted a prospective survey to assess women's knowledge of NIPT in those who had undergone NIPT (study group) and those who were planning to have NIPT (control group). Out of the 189 questionnaires analysed, the study group did not show a higher knowledge score compared to the control group (P = 0.097). 44% misunderstood that NIPT can identify more conditions than invasive testing, 69.8% were unaware of the recommended need for nuchal translucency measurement and 52.6% were unaware of the possibility of incidental findings. 31% even considered discussing termination of pregnancy as one of the next steps if NIPT shows high risk for Down syndrome. This study shows that current pre-test counselling is inadequate. Service providers should address these knowledge gaps and assist women to make informed choices.Impact Statement What is already known on this subject? Pre-test counselling for non-invasive prenatal testing (NIPT) should be conducted to assist women in making an informed consent. What do the results of this study add? Our results show that a significant proportion of women are unaware of the limitations of NIPT. What are the implications of these findings for clinical practice and/or further research? Service providers should improve their pre-test counselling focusing on areas of knowledge deficiencies and misunderstanding on NIPT identified in this study.